A Post-Western Europe: Strange Identities in a Less Liberal World Order. Issue 1 (7th March 2018) - Wæver, Ole
Abstract: Debates on "rising powers" and a possible end to the liberal international order mostly focus on two kinds of actors: the hegemon (the United States), privileged by the power distribution of yesteryear, and rising powers (notably China). Europe's curious position brings to light some intriguing dynamics of the emerging world order—nuances needed to capture a more differentiated future. This essay traces the threats and opportunities to Europe presented by the emerging order in four domains. In terms of overall power (polarity) and economics, far-reaching change registers but is rarely designated as threatening. In contrast, change regarding values (human rights and democracy especially) triggers more alarm. Finally, in the domain of institutions, change elicited a relative lack of concern prior to 2016, but worries have grown since then. For Europe, peaceful change primarily demands that rising powers rearticulate rather than confront classical Western values because, in contrast to the United States, there is little sense of loss in Europe in relation to the global structures of power and economics.